The Bearing Capacity Model of Pile Foundation with Hole-Drilling and Pile-Inserting Technology in Complex Geological Environments - Yi Wang; Guoyun Lu; En Zhang; Cheng Zhao; Wei Wang; Fenghui Dong (Buildings)
Karst geology creates a complex environment with diverse landforms, blurred boundaries, and multi-factor interactions. This paper presents a new drilling pile installation method: drill to a set depth, clean the hole, insert prefabricated piles, and drive or vibrate them to the target elevation. It suits tough geological conditions well. Pile foundations bear both axial and lateral eccentric loads. To explore prestressed high-strength concrete (PHC) pile foundations under eccentric vertical loads in karst areas, on-site bearing capacity tests were conducted. The results show that as load eccentricity increases, PHC pile foundation-bearing capacity drops notably. A finite element model was developed to analyze the stress and strain behavior of PHC pile foundations under eccentric loading in complex geological conditions, aiming to assess their bearing capacity and stability. Key findings include: (1) Under constant external load, the maximum displacement of the PHC pile foundation increases with greater load eccentricity. (2) Enhanced concrete strength reduces the maximum displacement of the pile foundation, while the peak stress remains stable. (3) The height of karst caves has a minimal impact on the bearing capacity and deformation of PHC pile foundations. These results highlight the importance of considering load eccentricity, concrete strength, and cave height in optimizing the design of PHC pile foundations for safety in complex geological settings.